Catalytic reaction of cytokinin dehydrogenase: preference for quinones as electron acceptors - Frébortová, Jitka; Fraaije, Marco W; Galuszka, Petr; Sebela, Marek; Pec, Pavel; Hrbác, Jan; Novák, Ondrej; Bilyeu, Kristin D; English, James T; Frébort, Ivo (The Biochemical journal, 2004)
The catalytic reaction of cytokinin oxidase/dehydrogenase (EC 1.5.99.12) was studied in detail using the recombinant flavoenzyme from maize. Determination of the redox potential of the covalently linked flavin cofactor revealed a relatively high potential dictating the type of electron acceptor that can be used by the enzyme. Using 2,6-dichlorophenol indophenol, 2,3-dimethoxy-5-methyl-1,4-benzoquinone or 1,4-naphthoquinone as electron acceptor, turnover rates with N6-(2-isopentenyl)adenine of approx. 150 s(-1) could be obtained. This suggests that the natural electron acceptor of the enzyme is quite probably a p-quinone or similar compound. By using the stopped-flow technique, it was found that the enzyme is rapidly reduced by N6-(2-isopentenyl)adenine (k(red)=950 s(-1)). Re-oxidation of the reduced enzyme by molecular oxygen is too slow to be of physiological relevance, confirming its classification as a dehydrogenase. Furthermore, it was established for the first time that the enzyme is capable of degrading aromatic cytokinins, although at low reaction rates. As a result, the enzyme displays a dual catalytic mode for oxidative degradation of cytokinins: a low-rate and low-substrate specificity reaction with oxygen as the electron acceptor, and high activity and strict specificity for isopentenyladenine and analogous cytokinins with some specific electron acceptors.
Keywords: kinetika; flavinadenindinukleotid; cytokininy; Cytokinins; Flavin-Adenine Dinucleotide; Protein Structure, Tertiary; katalýza; Aldehydes; Quinones; substrátová specifita; kukuřice setá; rekombinantní proteiny; Catalysis; Oxidation-Reduction; chinony; rostlinné proteiny; Electrochemistry; Zea mays; Oxidoreductases; Plant Proteins; Kinetics; Substrate Specificity; oxidace-redukce; elektrochemie; terciární struktura proteinů; Recombinant Proteins; aldehydy; oxidoreduktasy